Peran Edukasi Digital Oleh Influencer Kesehatan dalam Meningkatkan Kesadaran Gizi Anak pada Ibu Muda - Rahmadiana Rahmadiana; Tyas Kasusilaningrum (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Improving child health remains a key priority within the Sustainable Development Goals (SDGs), particularly in efforts to prevent stunting in Indonesia. As information-seeking behavior shifts from conventional to digital platforms, social media has emerged as a significant channel for health education. This study aims to analyze the digital communication strategies employed by health influencers, specifically the Instagram account @mizaafrizal, in educating young mothers on child nutrition. Using a descriptive qualitative approach, data were collected through content observation, in-depth interviews, and literature review. The findings indicate that Dr. Miza applies persuasive communication strategies based on active interaction, the use of relatable and friendly language, and the presentation of information supported by scientific evidence. His credibility as a medical professional, combined with an approachable and educational communication style, enhances message reception among young mothers. These results emphasize the role of health influencers as change agents in raising public awareness and understanding of child nutrition issues, contributing positively to digital-based health promotion efforts in Indonesia.